(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To find out the Anopheles species composition, distribution and human-biting activities of malaria vectors in three habitats, the residential area, the forest edge and the deep forest at Ea So nature reserve in Ea So commune, Ea Ka district, Dak Lak province Subjects and methods: Anopheles mosquitoes were collected by routine methods of the National Institute of Malaria - Parasitology - Entomology (2011) in June and November 2020 and May and November 2021. Results: A total of 13 species of Anopheles mosquitoes were collected in three habitats, including a residential area, forest edge, and deep forest at Ea So nature reserve, Ea So commune. An. dirus was collected at the forest edge and in the deep forest accounting for 2.42% and 97,58%, respectively, and An. dirus was not captured in the residential area. Only one An. minimus specimen was caught in the deep forest, accounting for 100%. The bitting time of An. dirus from 17h to 4h in the morning of the following day. Biting activity of An. dirus began very early from 17h-18h, peaking early between 18h-19h or 22h-23h. After 24h, the density of biting mosquitoes was low. Conclusions: An. dirus was collected in the deep forest habitat with high density in the rainy season and at the begining of the dry season. Biting activity of An. dirus began early, so it is necessary to recommend that forest-goers to use personal protection measures such as mosquito repellent cream, and mosquito coils... from early to protect from biting of this mosquito species.